(untitled) (Perioperaciina Medicina, 2023)
In this article, the authors discuss the place of modern analgesics of central action (nefopam hydrochloride) in the analgesia of patients with explosive injuries of the lower extremities. Currently, there is no information in global practice regarding the use of centrally acting analgesics for analgesia in patients with combat trauma. An example was the analgesia of patients in the p/o period with a severe explosive injury of the lower extremities. Attention is drawn to the need for effective analgesia for patients with a combo injury not only in the acute period. A feature of the treatment of such patients is the need for major restorative and reconstructive surgical interventions, which in turn are accompanied by a pronounced pain syndrome. In our experience, the addition of non-narcotic analgesics of central action (nefopam hydrochloride) to the scheme of multimodal analgesia is appropriate to improve analgesia in this category of patients. The addition of nefopam hydrochloride to a multimodal analgesia regimen at 20 mg IV every 6 hours was effective in the treatment of severe acute postoperative pain.